STRATEGI PEMBELAJARAN AKIDAH AKHLAK DI MI SUNAN KALIJOGO KARANGBESUKI MALANG - Ayu Dewi Citra Anggraini; Ika Ratih Sulistiani; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Subject of morality are one subjects that emphasize the ability to understand and defend beliefs, create an atmosphere of transparency and habituation by practicing praise and manners of sciences through the construction of examples, everyday behavior. In the moral faith often speakes of something abstract, so in order to teach it requires the proper selection of strategies so that what is taught by the teacher can be understood and well received by the learners. The strategy of learning in class five in Sunan Kalijogo Karangbesuki Malang is an expository learning strategy and cooperative learning strategy that can make student enthusiastic in learning because strategies that teachers use sexual beliefs are varied.Keywords: Learning strategy, Moral faith.